A Review Paper on Hadoop Architecture (International Journal of Innovative Research in Computer Science & Technology, 2021)
Hadoop is an open-source software programming platform for storing and processing huge  amounts of data. Its framework is built on Java  programming, with some native C code and shell scripts  thrown in for good measure. HDFS (Hadoop Distributed  File System) is a global; highly failure file system  intended to operate on low-cost commodity hardware.  Big Data is the term used to describe this massive amount  of data. In a world where data is generated at such a rapid  pace, it must be preserved, evaluated, and dealt with. It is  a subproject of the Apache Hadoop project. HDFS is  designed for operations with big data volumes and offers  high accessibility to application data. The main features  of HDFS are discussed in this article, as well as a high level overview of the HDFS structure. Hadoop is a  technology that will be used in the future, particularly by  big businesses. The quantity of data being generated is  only going to grow, and the need for this software is only  going to grow.
Keywords: Architecture; Big Data; Framework; Hadoop; HDFS